2016
DOI: 10.1111/psyp.12691
|View full text |Cite
|
Sign up to set email alerts
|

Where is the ball? Behavioral and neural responses elicited by a magic trick

Abstract: We present results from two experiments, in which subjects watched continuous videos of a professional magician repeatedly performing a maneuver in which a ball could “magically” appear under a cup. In all cases, subjects were asked to predict whether the ball would appear under the cup or not, while scalp EEG recordings were performed. Both experiments elicited strong and consistent behavioral and neural responses. In the first experiment, we used two blocks of videos with different probabilities of the ball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…We are aware of only three previous studies that investigated neural responses to the experience of magic tricks. The results of all three provide neural evidence that supports the notion of a relatedness between the "wow" effect as surprise signal and Bayesian predictive coding (Parris et al, 2009;Danek et al, 2015;Caffaratti et al, 2016).…”
Section: Neural Evidence For the "Wow" Effect As Surprisesupporting
confidence: 59%
See 3 more Smart Citations
“…We are aware of only three previous studies that investigated neural responses to the experience of magic tricks. The results of all three provide neural evidence that supports the notion of a relatedness between the "wow" effect as surprise signal and Bayesian predictive coding (Parris et al, 2009;Danek et al, 2015;Caffaratti et al, 2016).…”
Section: Neural Evidence For the "Wow" Effect As Surprisesupporting
confidence: 59%
“…More complex hierarchical Bayesian models of surprise can be used to model the "wow" effect of a large variety of tricks and to correlate these model-based predictions with both, behavioural and physiological measurements. This latter approach seems specially promising in view that only a handful of studies investigated the physiological effect of magic (Parris et al, 2009;Danek et al, 2015;Caffaratti et al, 2016). Crucially, a number of physiological signatures have been already related specifically to Bayesian surprise, such as pupil dilation (Zénon, 2019), the P300 evoked related potential in EEG (Mars et al, 2008;Wacongne et al, 2011;Kolossa et al, 2012;Kopp et al, 2016) and fMRI responses in the dorsal anterior cingulate cortex (Ide et al, 2013;O'Reilly et al, 2013;Schwartenbeck et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not attempt to define cognitive phenomena simply in terms of their neural correlates, since in that regard we still know next to nothing about the illusion of impossibility; recently, Caffaratti et al (2016) , have measured for the first-time specific changes in brain activity through electrophysiological records during the magician’s manipulations. In keeping with this, the few neuroimaging experiments that have so far measured changes in brain dynamics during the observation of magic effects have found that the same brain areas previously reported during problem solving and conflict monitoring tasks light up when the illusion of impossibility is experienced ( Parris et al, 2009 ; Danek et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%